Lipid Profile in Patients With Amyotrophic Lateral Sclerosis: A Systematic Review and Meta-Analysis - Liu, Jiao; Luo, Xiaoyue; Chen, Xueping; Shang, Huifang (Frontiers in Neurology, 2020)
Background: Studies have investigated the lipid profile in amyotrophic lateral sclerosis (ALS), including the levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and higher low-density lipoprotein (LDL), and the associations with mortality of ALS, but the results were inconsistent. Therefore, we conducted this meta-analysis to systematically answer this unsolved question. Methods: We searched all the related studies that probed into the association between serum lipid levels and ALS based on PubMed, EMBASE, and Cochrane library from January 1990 to July 2020. The quality of the included studies was evaluated by using the Newcastle–Ottawa Scale (NOS). All the statistical analyses of this meta-analysis were performed using the Stata version 12.0 software. Results: Fourteen studies with a total of 3,291 ALS patients and 3,367 controls were included. Among them, 10 studies compared the lipid profile between ALS patients and controls. The results indicated that compared with controls, ALS patients from both Europe and Asia had lower levels of TG and HDL, but the levels of TC and LDL were higher in ALS patients from Europe. However, after systemic analyses, the altered TC level was significant only in Asian ALS patients; the differences of other lipids were not significant. Concerning the effect of lipid profile on mortality of ALS, analyses of four cohort studies showed that the levels of all lipids were not associated with overall mortality in ALS. Conclusion: The results of the present study showed that Asian ALS patients had lower TC levels than controls, and the levels of all lipids were not associated with mortality of ALS.